Are the robots coming? Designing with autonomy & control for musical creativity & performance - Chamberlain, Alan (ACM, 2017)
This paper1 expands upon our previous work, and starts to unpack notions of autonomy and control in musical composition and performance-based systems. The term autonomous has become synonymous with technologies such as “autonomous vehicles” and “drones”, while notions of control have mainly been raised in respect to the “control” of industrial systems and in respect to protocols. This position piece disrupts these notions and provides a platform, introducing a more radical proposition in respect to the representation of autonomy and control of features that can be used to design systems that support musical composition and performance. This paper supports a growing interest within the Design, HCI and Artificial Intelligence communities, leading us to think about Human Like Computing systems and the development of a Computational Creativity Continuum.